Instilling Students' Character Values ​​of Responsibility Through Pancasila and Citizenship Education for Class XII IPS 3 Students at SMA Negeri 1 Muaro Jambi - Rahma Devi Indri; M Salam; Hendra Hendra (Journal of Education Technology Information Social Sciences and Health, 2024)
Character values are an education that describes how to bring out certain values from students. Certain values can be in the form of responsibility, attitude, tolerance, religion and so on. This research aims to describe how to instill the value of responsible character in students and describe the PPKn teacher's solution in instilling the value of responsible character through Pancasila and citizenship education in class XII IPS 3 students at SMA Negeri 1 Muaro Jambi. This research uses a qualitative approach and descriptive research type, using purposive sampling technique with data collection techniques, namely observation, interviews and documentation. Data analysis techniques use data reduction, data presentation and drawing conclusions. Based on the research results, basically every learning process has implemented the cultivation of the character value of responsibility for Pancasila and Citizenship Education subjects. The results of this research reveal that as a student whose task is to study every day at school, he should have the character value of responsibility, in accordance with the 9 indicators written by the Ministry of Education and Culture in 2018. PPKn teachers have an important role in instilling and forming the character of their students. Therefore, Civics teachers themselves must have good moral values themselves, have good creativity, have innovation in the learning process in order to create students who are intelligent, kind, have good character values, responsibility and other good things. From the results of this research, things that students can do as students include doing assignments given by the teacher and trying to do it themselves, coming to school on time, taking responsibility for mistakes they have made, participating in extracurricular and social activities at school, carrying out school obligations. active in learning and able to solve a problem in class/group and so on.